Modelagem de distribuição potencial, impactos ambientais e econômicos do Aguapé (Eichhornia crassipes) - Pedro Fialho Cordeiro (2018)
Species Distribution Models (SDM) are tools for predicting the potential distribution of a specie through the relationship between occurrence data and environmental conditions. One of the most recent applications are the predicting spread of invasive plants, such as E. Crassipes (water hyacinth). This species occupies a list of the International Union for the Conservation of Nature (IUCN) of the 100 worst invasive species and the Top 20 of the spanish group of specialists in biological invasions. Actions that prevent their dispersion should be sought as they represent a more efficient and low-cost approaches. The objective of this study is to elaborate a potential distribution model of water hyacinth to support an assessment of the invasion potential for non-colonized areas, pointing areas of risk in terms of threats to habitat biodiversity, human supply and shipping at global scale. The MaxEnt - Maximum Entropy algorithm was used in the construction of the model and included five bioclimatic layers and one of urban spots worldwide. The distribution models are consistent with the current points of presence of the species used in the study, as well as administrative regions in which the water hyacinth has populations established in their native habitat or in the invaded countries. Threats posed by this plant are possibly more acute in regions suffering from chronic drought. Global biodiversity hotspots are predominantly situated in appropriate high suitability regions. Ramsar sites and global conservation units are in a more secure situation, but scenarios of climate change and the growth of megacities can put them at risk of invasion. It is suggested a more detailed individual evaluation for areas, to categorize them according to the environmental suitability in which they are located and in relation to records of presence records of E. crassipes. Understanding the potential of invasion of this species is crucial to involve the management of the species and to avoid negative impacts. The methodology applied in this work can be used to evaluate the spreading potential of other invasive species.